(untitled) (Revista Brasileira Multidisciplinar, 2019)
Plant growth biostimulants are used in seed treatment because they increase the percentage and speed of germination The objective of this work was to evaluate the germination of bean seeds (Phaseolus vulgaris L.), BRS Esteio cultivar, pre-soaked in different doses of a commercial biostimulant, composed of 50 mg L-1 of indolebutyric acid, 90 mg L-1 of kinetin and 50 mg L-1 of gibberellic acid. The treatments were: 7.5 mL, 10 mL, 25 mL and 50 mL of biostimulant per kg of seeds and a control treatment with pre-soaking in sterile distilled water. It was evaluate the germination rate (%), germination velocity index (IVG), mean shoot length (CMPA), mean root length (CMR), fresh shoot biomass (BFPA), dry shoot biomass BSPA), fresh root biomass (BFR) and dry root biomass (BSR) of germinated seeds. The dose of 10 mL kg-1 of seed had the highest percentage of germination (84%) and the highest IVG. The same treatment showed significantly higher mean values for CMPA, CMR, BFR and BSR. BFPA and BSPA were negatively affected by biostimulant pre-soaking. It was concluded that the dose of 10 mL of biostimulant per kg of seeds resulted in a higher percentage and speed of germination, shoot and root lengthening, and increase of fresh and dry biomass of the roots, while the different dosages of biostimulant in the treatment of bean seeds provided a decrease in the accumulation of fresh and dry shoot biomass in the germinated seeds.